Using postoperative remodeling of donor arteries on MR angiography to predict the development of surgical collaterals in moyamoya disease - Uchino, Haruto; Yamamoto, Shusuke; Kashiwazaki, Daina; Akioka, Naoki; Kuwayama, Naoya; Noguchi, Kyo; Kuroda, Satoshi (Journal of neurosurgery, 2021)
The calibers of donor arteries can change dynamically after bypass surgery in patients with moyamoya disease (MMD). The present study aimed to evaluate the cutoffs of caliber changes in donor arteries associated with good surgical revascularization and to assess the impact of clinical factors potentially related to bypass development. The authors studied 71 hemispheres of 30 adults and 16 children with MMD who underwent combined direct and indirect revascularization. They quantitatively measured the calibers of the superficial temporal artery (STA), deep temporal artery (DTA), and middle meningeal artery (MMA) with MR angiography (MRA) source images and calculated the postoperative caliber change ratios (CCRs) to assess direct and indirect bypass development. These values were compared with the findings of digital subtraction angiography, in which revascularization areas were categorized into 3 groups (poor, good, and excellent). In both adult and pediatric hemispheres, the median STA and DTA CCRs were higher in better-revascularization groups (p < 0.05), while MMA CCRs were not significantly different among the groups. Receiver operating characteristic analysis revealed that the cutoff STA CCRs of > 1.1 and > 1.3 were associated with good direct revascularization in adult and pediatric hemispheres, respectively. Cutoff DTA CCRs of > 1.6 and > 1.2 were associated with good indirect revascularization in adult and pediatric hemispheres, respectively. Considering these cutoff values, STA and DTA CCRs showed high median values, irrespective of age, severity of cerebrovascular reserve, disease stage, and disease-onset type. Caliber changes in STAs and DTAs can be easily measured using MRA, and they could be indicators of direct and indirect bypass development. The dual development of a direct and indirect bypass was most frequently observed in the context of a combined bypass procedure in both adults and children with MMD.